Insulin resistance markers HOMA-IR, TyG and TyG-BMI index in relation to heart failure risk: NHANES 2011-2016 - Meijuan Lu; Junchi Guo; Peili Yang; Teng Ma; Mingyan Zhang (PLoS ONE, 2025)
Background Insulin resistance (IR) is increasingly recognized as an important factor in the development of heart failure (HF). This study aimed to evaluate the association and predictive ability of three IR markers—HOMA-IR, TyG, and TyG-BMI index—with HF risk. Methods Data from 7,668 participants in the NHANES 2011–2016 survey were analyzed. Multivariable logistic regression was used to assess the relationship between HOMA-IR, TyG, and TyG-BMI with HF incidence, adjusting for potential confounders. Receiver operating characteristic (ROC) curves, decision curve analysis (DCA), and restricted cubic spline (RCS) analysis were conducted to compare the predictive performance of the three markers. Results HOMA-IR (OR = 1.017, 95% CI: 1.006–1.027, P < 0.01), TyG (OR = 1.798, 95% CI: 1.453–2.225, P < 0.001), and TyG-BMI (OR = 1.006, 95% CI: 1.004–1.008, P < 0.001) were all significantly associated with HF risk, with TyG showing the strongest association. ROC curve analysis demonstrated that TyG (AUC = 0.61) and TyG-BMI (AUC = 0.62) had better predictive abilities than HOMA-IR (AUC = 0.6). In subgroup analyses, HOMA-IR showed higher sensitivity in the female population, while TyG-BMI provided a complementary role to TyG in individuals with diabetes. Conclusion TyG showed a stronger association with HF risk than HOMA-IR and TyG-BMI and outperformed HOMA-IR in predicting HF risk, particularly in specific subpopulations. These findings highlight the importance of further research into the clinical application of TyG for early identification and management of HF risk.